PERAN KOMUNITAS PRAMUWISATA BADUY LUAR DALAM MEMPERTAHANKAN KEARIFAN LOKAL - Firdaus, Muhammad Nova; Budiaman; Herminasari, Nova Scorviana (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2020)
This study aims at obtaining data on the role of the community of Baduy Luar guides in an effort to maintain local wisdom along with socio-cultural changes that occur in the Baduy Luar village, Kanekes Village, Lebak Regency, Banten. The researcher uses a qualitative approach. Data collection techniques are carried out by semi-structured interviews, observations, analysis of documents and field notes. The results of the study concluded that the tourism services carried out by the HPI-DPU Baduy were still very simple in general but were in accordance with the concept of tourism services, starting from transfers, guiding tours, and transfer out. The concept of service they are doing is directly related to their strategy in maintaining local wisdom. Their role is at least in the three dimensions of local wisdom, namely: (1) local values; (2) local resources; and (3) local group solidarity. The socio-cultural changes that occur in the Baduy Luar community in the tour community are caused by several factors. Internally, changes occur because of Baduy’s people attitude who are increasingly open. Then externally, changes occur because the Baduy people interact more intensively with outside communities such as meeting tourists, trading, participating in training and farming outside their area.